Deactivation and regeneration of Pt-modified zeolite Beta-Bindzil extrudates in n-hexane hydroisomerization - Vajglova Zuzana; Kumar Narendra; Peurla Markus; Hupa Leena; Semikin Kirill; Sladkovskiy Dmitry A.; Murzin Dmitry Yu (WILEY, 2022)
BACKGROUND The metal-acid bifunctional catalysts are widely used in many industrially significant chemical processes, including hydroisomerization of n-hexane. Deactivation and regeneration of metal-acid bifunctional extrudates was investigated in continuous n-hexane hydroisomerization in a fixed-bed reactor. Four Pt/H-Beta-25 catalysts containing 30% Bindzil binder were prepared with the same composition and controlled metal deposition.RESULTS Different preparation steps led to differences in the mechanical strength, Pt particle size, acidity and strength, metal-to-acid site (c(Pt)/c(AS)) ratio and proximity between two types of active sites. A very slow deactivation and high selectivity to C-6 isomers was obtained when Pt was deposited on H-Beta-25 zeolite.CONCLUSION Initial selectivity to the desired products was correlated with the physicochemical properties of the catalysts. Location of the metal has a larger influence on catalyst deactivation of the bifunctional catalysts rather than the metal-to-acid site ratio or site proximity. Decline of n-hexane conversion and selectivity to C-6 isomers were correlated with changes in the textural properties and acidity of the deactivated catalyst, respectively. (c) 2021 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.